Diagnosis of valvular heart disease through neural networks ensembles - Das, Resul; Turkoglu, Ibrahim; Sengur, Abdulkadir (Elsevier Ireland Ltd, 2009)
In the last decades, several tools and various methodologies have been proposed by the researchers for developing effective medical decision support systems. Moreover, new methodologies and new tools are continued to develop and represent day by day. Diagnosing of the valvular heart disease is one of the important issue and many researchers investigated to develop intelligent medical decision support systems to improve the ability of the physicians. In this paper, we introduce a methodology which uses SAS Base Software 9.1.3 for diagnosing of the valvular heart disease. A neural networks ensemble method is in the Centre of the proposed system. The ensemble-based methods creates new models by combining the posterior probabilities or the predicted values from multiple predecessor models. So, more effective models can be created. We performed experiments with proposed tool. We obtained 97.4% classification accuracy from the experiments made on data set containing 215 samples. We also obtained 100% and 96% sensitivity and specificity values, respectively, in valvular heart disease diagnosis. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Doppler heart sounds; Heart valves; Neural networks; Ensemble-based method; SAS base software